The feasibility of virtual reality for anatomic training during temporal bone dissection course - Timonen, Tomi; Iso-Mustajärvi, Matti; Linder, Pia; Vrzakova, Hana; Sinkkonen, Saku T.; Luukkainen, Veera; Laitakari, Jaakko; Elomaa, Antti-Pekka; Dietz, Aarno (Frontiers in Virtual Reality, 2022)
Introduction In recent decades, the lack of educational resources for cadaveric dissections has complicated the hands-on otological surgical training of otorhinolaryngology residents due to the poor availability of cadaver temporal bones, facilities and limited hours for practice. Since students must gain adequate and patient-safe surgical skills, novel training methods need to be considered. In this proof-of-concept study, a new virtual reality (VR) software is described; this was used during a national temporal bone dissection course where we investigated its feasibility for otologic surgical training. Methods A total of 11 otorhinolaryngology residents attended the annual two-day hands-on temporal bone dissection course; they were divided into two groups with similar experience levels. Both groups received a lecture on temporal bone anatomy. Twenty-two cadaver temporal bones were harvested for the course; eleven of these bones were imaged by computed tomography. VR software designed for preoperative planning was then used to create 3D models of the imaged temporal bones. Prior to dissection training, the first group underwent a 30min VR-session, where they identified 24 surgically relevant anatomical landmarks on their individual temporal bone. The second group proceeded directly to dissection training. On the second day, the groups were switched. The feasibility of VR training was assessed with three different metrics: surgical performance evaluation using a modified Hopkins Objective Structured Assessment of Technical Skill (OSATS), time for the surgical exposure of anatomical landmarks and the user-experience collected with a Likert scale questionnaire. Results No differences were noted in the overall performance between the groups. However, participants with prior VR training had a lower mean time for surgical exposure of anatomical landmarks (antrum 22.09 vs. 27.64 minutes, p=0.33; incus 60.00 vs. 76.00, p=0.03; PSCC 71.83 vs. 88.50, p=0.17) during dissection training. The participants considered VR as beneficial for anatomy teaching, surgery planning and training. Conclusion This study demonstrated the feasibility of implementing VR training in a temporal bone dissection course. The VR training demonstrated that even short expert-guided VR sessions are beneficial and VR training prior to the dissections exerts a positive effect on the time needed to perform surgical tasks while maintaining comparable performance scores.